A Novel Mass-Spring-Damper Model Analysis to Identify Landing Deficits in Athletes Returning to Sport After Anterior Cruciate Ligament Reconstruction. Issue 9 (September 2017) - Schneider, Daniel K.; Gokeler, Alli; Otten, Egbert; Ford, Kevin R.; Hewett, Timothy E.; Divine, Jon G.; Colosimo, Angelo J.; Heidt, Robert S.; Myer, Gregory D.
Abstract : Abstract: Schneider, DK, Gokeler, A, Otten, E, Ford, KR, Hewett, TE, Divine, JG, Colosimo, AJ, Heidt, RS, and Myer, GD. A Novel mass-spring-damper model analysis to identify landing deficits in athletes returning to sport after anterior cruciate ligament reconstruction. J Strength Cond Res 31(9): 2590–2598, 2017—A mass-spring-damper (MSD) model may serve as an extension of biomechanical data from 3-dimensional motion analysis and epidemiological data which helps to delineate populations at risk for anterior cruciate ligament (ACL) injuries. The purpose of this study was to evaluate such a model. Thirty-six ACL reconstruction (ACLR) group subjects and 67 controls (CTRL) completed single-leg drop landing and single-leg broad jump tasks. Landing ground reaction force data were collected and analyzed with an MSD model. Medians, interquartile ranges, and limb symmetry indices (LSIs) were calculated and comparisons were made within and between groups. During a single-leg drop landing, the ACLR group had a lower spring LSI than the CTRL group ( p = 0.015) and landed with decreased stiffness in the involved limb relative to the uninvolved limb ( p = 0.021). The ACLR group also had an increased damping LSI relative to the CTRL group ( p = 0.045). The ACLR subjects landed with increased stiffness ( p = 0.006) and decreased damping ( p = 0.003) in their involved limbs compared to CTRL subjects' nondominant limbs. During a single-leg forward broad jump, the ACLR group had a greater spring LSI value than the CTRL group ( p = 0.045). The CTRL group also recorded decreased damping values in their nondominant limbs compared with the involved limbs of the ACLR group ( p = 0.046). Athletes who have undergone ACLR display different lower-limb dynamics than healthy controls, according to an MSD model. Quadriceps dominance and leg dominance are components of ACLR athletes' landing strategies and may be identified with an MSD model and addressed during rehabilitation.